SEVERAL APPROACHES TO TRAFFIC ASSIGNMENT (Perner's Contacts, 2009)
The objective of this paper is to introduce Traffic Assignment problem. Theproblem is stated; miscellaneous variants are specified. The most common methodsare briefly described and compared using model example.
Keywords: Traffic Assignment; User Equilibrium; Algorithms